The Application of the K-Nearest Neighbor (KNN) Method to Determine House Locations in the Batuphat and Tambon Tunong Areas, Aceh - Khairi, Abil; Fahrezi, Irgi; Sahputra, Irfan; Anshari, Said Fadlan (Journal of Advanced Computer Knowledge and Algorithms, 2024)
This study aims to apply the K-Nearest Neighbors (KNN) method to find the location of a house situated precisely on the border between Batuphat and Tambon Tunong. The issue faced by the college friends is the difficulty in determining whether the house falls within the Batuphat or Tambon Tunong area. The KNN method is used due to its ability to classify based on the nearest neighbors' distance.The data used in this research includes information on the house's location and the Batuphat and Tambon Tunong areas. The training process is conducted to form the KNN model based on the known location data, while the testing process is employed to classify the unknown house location into either the Batuphat or Tambon Tunong area.The results of the study demonstrate that the KNN method can be utilized to determine the location of a house situated on the border between Batuphat and Tambon Tunong. By considering the nearest neighbors' distance, the house can be classified into one of the areas with a high level of accuracy.This research contributes to providing a solution for college friends who face difficulties in determining the house location on the Batuphat and Tambon Tunong border. The KNN method can serve as an effective tool in addressing this problem. Moreover, this study can serve as a basis for further development in the field of location classification based on the KNN method.